Management of AI Chatbots to Improve Student Achievement in an Indonesian Senior High School - Ika Subandi; Abdulloh; Ine Rahayu Purnamaningsih (Didaktika: Jurnal Kependidikan, 2026)
The integration of artificial intelligence (AI) in education has increasingly been adopted to support digital learning environments; however, the effectiveness of AI chatbot implementation largely depends on how it is managed within schools. This study aims to analyze the management of AI chatbots in enhancing student academic achievement at SMAN 1 Cikarang Pusat. The research employs a descriptive qualitative case study approach. Data were collected through observations, semi-structured interviews, and documentation involving the school principal, teachers, IT staff, and students. The findings show that the school has implemented AI chatbots as part of its digital learning innovation through several management stages: (1) planning, including needs analysis, infrastructure preparation, and teacher training; (2) implementation in learning activities such as practice exercises, enrichment materials, and academic consultations; and (3) monitoring and evaluation conducted by teachers and IT personnel. The results indicate that the use of AI chatbots contributes to increased student learning motivation, more flexible access to learning resources, and improved independent learning habits. Nevertheless, several challenges remain, including differences in teacher digital literacy, the lack of standardized operational procedures, and unequal access to digital devices and internet connectivity among students. This study contributes to the development of AI-based learning management practices by providing practical insights for schools in managing chatbot technology effectively to support student academic performance in the digital era.